Investigation on cation distribution and luminescence in spinel phase gamma-Ga3-delta O4 : Sm nanostructures using X-ray absorption spectroscopy - Sharma, Aditya; Varshney, Mayora; Shin, Hyun-Joon; Chae, Keun Hwa; Won, Sung Ok (ROYAL SOC CHEMISTRY, 2017)
In this study, spectroscopic investigations are employed to quantify the Ga distribution over the tetrahedral/octahedral sites and to assimilate the luminescence properties in the barely reported gamma-Ga2.67O4 : Sm nanoparticles. O K-edge XANES are convincing the decreased electron density in the outermost hybrid orbits of O 2p and Ga 4p, and the movement of p electrons to the inner hybrid orbits with s character under the distorted oxygen environment of gamma-Ga2.67O4 : Sm nanoparticles. The Ga K/L-edge XANES and Sm L-3/M-5,M-4-edge XANES results have confirmed Ga3+ and Sm3+ ions, respectively, in the gamma-Ga2.67O4 : Sm nanoparticles. Quantitative determination of the cation distribution is performed by applying Ga K-edge XANES data analysis, which is further substantiated by an EXAFS data simulation, and conveys a Ga-O4 tetrahedra/Ga-O6 octahedra ratio (Ga(t)/Ga(o)) of similar to 0.9, similar to 1.4, similar to 1.5 and similar to 1.6 for the beta-Ga2O3, gamma-Ga2.67O4, gamma-Ga2.67O4 : 5Sm and gamma-Ga2.67O4 : 10Sm samples, respectively, which signify the Sm doping induced deformation of Ga-O6 octahedra via the formation of oxygen defects. Multiple luminescence centres, facilitated by the Ga-O6 octahedra distortion, O vacancies and Sm3+ ions, have helped in a significant enhancement of the emission characteristics. Our spectroscopy investigations, with the help of XANES and EXAFS, may open new opportunities to the mechanistic understanding of metal-O polyhedra alteration induced fruition of physical/chemical properties in the less explored meta stable phases of other complex oxides.
Keywords: GALLIUM OXIDE; ELECTRONIC-STRUCTURE; MECHANISTIC INSIGHTS; THIN-FILMS; NANOPARTICLES; PHOTOLUMINESCENCE; XANES; EXAFS; EDGE; TEMPERATURE